4-Hydroxy-2-nonenal causes nuclear accumulation of p62 by inhibiting Xpo1 and promoting the proteolytic pathway in the nucleus. - Emi Kayama; Ning Baoshuo; Rinna Tatsuno; Kanako Nishi; Elsayed S I Mohammed; Yumi Abiko; Toru Yanagawa; Satoru Takahashi; Eiji Warabi (PLoS ONE)
p62, an adapter protein involved in selective autophagy, is mainly found in the cytoplasm under normal conditions. Because p62 has nuclear localization signal (NLS) and a nuclear export signal, it has been suggested that p62 shuttles between the nucleus and cytoplasm. We studied the effect of 4-hydroxy-nonenal (4-HNE), an endogenous lipid peroxidation product, on intracellular p62 distribution in mouse embryonic fibroblasts. We found that treatment of 4-HNE causes p62 translocation from the cytoplasm to the nucleus. Further analysis revealed that 4-HNE directly binds to exportin-1 (Xpo1), essential protein for nuclear export of various proteins. Further analysis 4-HNE enhanced intranuclear EGFP-NLS-CL1 degradation in a p62-dependent manner. Our results suggest that 4-HNE changes p62 localization to the nucleus by inhibiting Xpo1 and might affect intranuclear protein quality control.